Strategi Edukasi Anti-Bullying Anak Usia Dini melalui Psikoedukasi di RPTRA Satria Jelambar - Alia Firda Rayani; Anastasya Dumyanti; Okta Febri Lestari; Raja Oloan Tumanggor (Jurnal Pendidikan dan Sastra Inggris, 2025)
The prevalence of bullying among children in Indonesia is estimated to be increasing, particularly among those aged 7 to 11 years. According to the Global School-based Health Survey (GSHS), more than 40% of elementary school-aged children in Indonesia have experienced bullying. Bullying is defined as aggressive behavior that is repeated over time and directed toward individuals perceived as weaker, with the intent to cause harm physically, verbally, nonverbally, or through digital platforms. This community service program aimed to provide anti-bullying education through a psychoeducational approach combined with educational play. The participants consisted of 23 children aged 7–11 years at RPTRA (Child-Friendly Integrated Public Space) Satria Jelambar. The program was implemented in three stages: preparation, execution (through psychoeducation and interactive games), and evaluation. Its effectiveness was assessed using a pretest-posttest design with questionnaires, and the data were analyzed descriptively. The results indicated that the anti-bullying education program was effective in increasing children’s understanding of bullying and encouraging more positive social behavior in play environments, making it a promising early prevention strategy.